Expansion in Eigenfunctions of Relations Generated by Pair of Operator Differential Expressions - Khrabustovskyi, V. (Інститут математики НАН України, 2009)
For relations generated by a pair of operator symmetric differential expressions, a class of generalized resolvents is found. These resolvents are integro-differential operators. The expansion in eigenfunctions of these relations is obtained.